Patrimônio documental: preservando o acervo fotográfico do Khadro Ling - Cunha, Catherine da Silva (2013)
The present study has its theme the preservation and dissemination of the photographic collection of Khadro Ling, Buddhist Temple , located at Três Coroas , Rio Grande do Sul. Consists of an exploratory research about their goals and applied as to its purpose. General aims to propose a suitable methodology to the preservation and dissemination of the photographic collection by developing recommendations for their preservation; deployment of a digital repository, and the production of a catalog of photographs for the selective heritage education of visitors the Khadro Ling. Justified by the extensive use of imagistic representations in Tibetan Buddhism, the exceptionality of the existence of a traditional temple in the state of Rio Grande do Sul , and the large number of visitors it receives . It is based on the theoretical framework for the conservation of photographic archives in paper and digital format, the diffusion of institutional memory and image as equity. As a result, it was identified that the main needs and expectations related to the organization and preparation of the photographs in the paper. As the deployment of a digital repository, showed the limitations of a project with little time to run forward budget possibilities and planning a nonprofit institution. Finally, we used the feature Prezi for the preparation of selective catalog of photographs for the visitors of heritage education in the form of an electronic guide. It was concluded that the only significant risks to the photographs found in paper referred to the packaging material inappropriate and constant exposure to artificial light, and that the actions taken have contributed to the photographs could fulfill his role in safeguarding and redeeming the institutional history as well as its role as documentary heritage closer to the viewer of cultural signs representing.